Tourists' intention to visit green hotels: Building on the theory of planned behaviour and the value-belief-norm theory - Muhammad Ashraf, Fauzi; Mohd Hafiz, Hanafiah; Velan, Kunjuraman (Emerald Group, 2022)
Purpose; This study integrates the theory of planned behaviour (TPB) and value-belief-norm (VBN) theory to investigate tourists' intention and behaviour to visit green hotels in Malaysia. Design/methodology/approach; A total of 160 valid questionnaire responses were collected via an online survey. The partial least square–structural equation modelling (PLS-SEM) technique was utilised to assess the study framework and the hypothesised relationship. Findings; The study's results confirmed that tourists' intention to stay at a green hotel is directly influenced by their subjective norms and perceived behavioural control. Besides, the study confirms the insignificant relationship between green trust, personal norms and tourists' stay intention. On the other hand, perceived morals, responsibility, willingness to pay more and perceived consumer effectiveness were significant in explaining the customer's subjective norms, personal norms and perceived behaviour control. Research limitations/implications: The hotel industry may benefit from this empirical outcome to devise effective marketing strategies for retaining their customers, particularly in rejuvenating the impact of the COVID-19 pandemic on the industry. Practical implications: This study provides valuable practical implications for green hotel operators to develop effective strategies to attract tourists to green hotel visits. Originality/value: This study is the first to integrate the extended TPB and VBN theory to understand tourist intention to visit a green hotel. Notably, the extended TPB and VBN theory was practical and helpful in predicting tourist intention to visit a green hotel.